2001
DOI: 10.1099/00221287-147-3-527
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic consequences of red–white colony type variation in Mycobacterium avium

Abstract: Mycobacterium avium undergoes reversible morphotypic switching between the virulent transparent colony type and the less virulent opaque colony type. A new morphotypic switch in M. avium, termed red-white, that becomes visible when opaque colonies of clinical isolates are grown on agar media containing Congo red, was recently described. White opaque (WO) variants were found to be more resistant to multiple antibiotics than were red opaque (RO) variants. The present paper reports that transparent derivatives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 18 publications
2
46
0
2
Order By: Relevance
“…The rough strain, completely devoid of GPLs, did not spread, while another rough strain which was able to synthesize incomplete GPLs produced smaller spreading areas. In addition to these results, Cangelosi et al have reported that when M. avium grows in agar media containing Congo red, new phenotypic variations can be detected since smooth strains give pink, red, and white colonies (4). These authors detected that red variants spread more aggressively than white ones, but no data about the content of GPLs or other compounds responsible for the different behaviors between the two morphotypes were provided.…”
mentioning
confidence: 89%
“…The rough strain, completely devoid of GPLs, did not spread, while another rough strain which was able to synthesize incomplete GPLs produced smaller spreading areas. In addition to these results, Cangelosi et al have reported that when M. avium grows in agar media containing Congo red, new phenotypic variations can be detected since smooth strains give pink, red, and white colonies (4). These authors detected that red variants spread more aggressively than white ones, but no data about the content of GPLs or other compounds responsible for the different behaviors between the two morphotypes were provided.…”
mentioning
confidence: 89%
“…avium has been shown to undergo red-white morphotypic switching when grown on agar media containing Congo Red. 28,34 White opaque variants were found to be more resistant to multiple antibiotics than red opaque variants.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent variants of M. avium subsp. avium predominate in clinical samples, 28 whereas opaque variants in general have been shown to be better adapted for growth in the laboratory and tend to predominate after multiple passages. [29][30][31][32][33] In addition, M. avium subsp.…”
Section: Introductionmentioning
confidence: 99%
“…As micobactérias, bactérias do gênero Mycobacterium, são bacilos álcool-ácido resistentes (BAAR), de crescimento lento (GYLES;THOEN, 1986;TIMONEY et al, 1988;INDERLIED et al, 1993;FALKINHAM III, 1996), com 0,2 a 0,7 μm de largura e um a 10 μm de comprimento, aeróbios, imóveis, não esporulados (HOLT et al, 1994) e não pigmentados que têm crescimento otimizado em pH 5 a 5,5 em microaerofilia, em águas salobras ou não (FALKINHAM III, 1996) e são intrinsecamente resistentes a drogas (INDERLIED et al, 1993;REDDY, 1998;CANGELOSI et al, 2001;COSMA et al, 2003) e a vários desinfetantes químicos (EVERITT et al, 1982 RICHTER et al, 2003;CHIMARA et al, 2004).…”
Section: Lista De Símbolos 1 Introduçãounclassified
“…A variação reversível e transitória na morfologia das colônias de M. avium tem importância significante para a virulência, patogenia e susceptibilidade a antibióticos desses microrganismos (REDDY et al, 1996). As variantes lisas opacas normalmente são isoladas do ambiente e crescem bem em meios de cultura (REDDY et al, 1996;CANGELOSI et al, 2001); as lisas transparentes, mais virulentas que as lisas opacas (REDDY et al, 1996;REDDY, 1998;CANGELOSI et al, 2001), predominam em amostras clínicas, crescem melhor em macrófagos e modelos animais (CANGELOSI et al, 2001), colonizam eficientemente as mucosas, aderem facilmente às células epiteliais e são mais resistentes aos antibióticos (REDDY et al, 1996;REDDY, 1998;CANGELOSI et al, 2001); as intermediárias podem sobreviver e prosperar sob condições adversas. As variantes rugosas podem surgir após passagem in vitro, mas são desconhecidas as condições que favorecem seu crescimento (CANGELOSI et al, 2001).…”
Section: Lista De Símbolos 1 Introduçãounclassified